The Comprehensive Systematic Review of Fluid Overload and Mortality in Critically Ill Children - Mohamad Fadli; Raka Jati Prasetya; Mutia Juliana (The Indonesian Journal of General Medicine, 2026)
Introduction: Fluid overload (FO) is a common complication in critically ill children associated with adverse outcomes. However, heterogeneity in definitions, measurements, and study populations has created gaps in understanding the true magnitude of this association. This systematic review aims to comprehensively synthesize evidence on the association between FO and mortality in critically ill children, examining definitions, measurement methods, and population-specific effects. Methods: A systematic review of observational studies, randomized controlled trials, and meta-analyses examining FO and mortality in critically ill children (0-18 years) admitted to PICUs, NICUs, or cardiac ICUs was conducted. Studies were screened based on predefined criteria including pediatric population, FO exposure with clear definition, mortality outcomes, and adequate sample size. Data extraction encompassed study characteristics, FO definitions, mortality outcomes, confounding adjustments, secondary morbidity outcomes, and methodological quality. Results: Sixty-five studies were included, comprising over 45,000 patients across general PICUs, cardiac ICUs, and specialized populations (sepsis, CRRT, ECMO, ARDS, TBI). FO definitions varied considerably, with percentage FO calculated as (fluid intake—output)/reference weight × 100 being most common. Thresholds ranged from ≥5% to ≥20%, with reference weights including admission, preoperative, or dry weight. Meta-analyses demonstrated significantly increased mortality with FO (pooled OR range: 4.34-5.06). A dose-response relationship was consistently observed, with 3-6% increased mortality odds per 1% FO increase. Mortality rates were consistently higher across FO thresholds: 29.4% vs. 65.6% for <10% vs. ≥20% FO in CRRT patients; 46% vs. 26% for >10% FO in sepsis. However, 4 studies found no independent association after multivariable adjustment. Secondary outcomes including prolonged mechanical ventilation, longer PICU/hospital stays, and AKI were consistently associated with FO. Discussion: This review demonstrates a consistent, dose-dependent association between FO and mortality across diverse pediatric critical care populations, though with important population-specific variations. The strongest associations were observed in sepsis, CRRT, ECMO, and post-cardiac surgery patients, while TBI showed inconsistent findings. The timing of FO assessment emerged as critical, with later-onset FO (>48-72 hours) showing stronger mortality associations. Methodological heterogeneity in FO definitions and measurement remains a significant limitation. Conclusion: Fluid overload is independently associated with increased mortality and morbidity in critically ill children, with evidence supporting a dose-response relationship. Standardized FO definitions and measurement protocols are urgently needed. Future research should focus on randomized trials of fluid management strategies and risk-stratified approaches.